Islamic Criminal Law View of the Money Doubling Scam (Study of Court Judgment Number 238/Pid/2018/Pt Sby) - Putri Hilma Badri Yanti (CLEAR: Criminal Law Review, 2023)
Law is a regulation regarding human behavior in socially coercive behavior. One of the violations of the law in Indonesia is a criminal act of fraud this criminal act of fraud is a crime against property as regulated in the Book of II KUHP in chapter XXV.  In thus case, the author conducts a study on the verdict of a criminal act as in the case of the Surabaya High Court Decision Number 238/PID/2018/PT SBY. The defendant Dimas Kanjeng is subject to Article 378 of the Criminal Code jo. Articel 64 paragraph (1) of the Criminal Code jo. Articel 64 paragraph (1) of the Criminal Code jo. Articel 12 paragraph (4) of the Criminal Code in conjuncition with Articel 66 paragraph (1) of the Criminal Code. The defendant legally committed the criminal act of “continuing fraud” based on the Decision of the Surabaya District Crout judge against Dimas Kanjeng in the from of a sentence of Zero. Becouse he is the highest leader and the Great Teacher of Padepokan should not do that Abstrak Hukum ialah suatu peraturan mengenai perilaku manusia dalam tingkah laku pergaulan masyarakat yang bersifat memaksa. Pelanggaran hukum di Indonesia salah satunya adalah tindak pidana penipuan yang mana tindak pidana penipuan ini merupakan kejahatan terhadap harta benda yang diatur dalam Buku II KUHP dalam Bab XXV. Dalam hal ini penulis melakukan kajian atas putusan tindak pidana sebagaimana kasus dalam putusan Pengadilan Tinggi Surabaya Putusan Nomor 238/PID/2018/PT SBY. Terdakwa Dimas Kanjeng dikenai pasal 378 KUHP jo. Pasal 64 ayat (1) KUHP jo. Pasal 12 ayat (4) KUHP jo Pasal 66 ayat (1) KUHP. Terdakwa secara sah menurut hukum melakukan tindak pidana “penipuan dengan berlanjut” berdasarkan Putusan Majelis Hakim Pengadilan Negeri Surabaya terhadap Dimas Kanjeng berupa pidana selama Nihil. Karena ia adalah pimpinan tertinggi dan Guru Besar Padepokan tidak sepatutnya melakukan hal demikian.